First principles study in two-dimensional antiferromagnetic Mn2Cl8 with strain-controllable and hydrogenation - Michang Zhang; Zhicui Wang; Yong Wei; Wenhui Wan; Yong Liu; Yanfeng Ge (Materials Research Express, 2023)
With the rapid development of spintronics, two-dimensional antiferromagnetic materials have attracted much attention because of their unique physical properties. Here, the monolayer Mn _2 Cl _8 is discovered to be an intrinsically antiferromagnetic semiconductor in current work. The results show that monolayer Mn _2 Cl _8 and Mn _2 Cl _4 X _4 (X = F, Br) are stable semiconductors with indirect bandgaps of 0.34eV, 0.95eV, and 0.55eV, respectively, and Mn _2 Cl _8 has a Néel temperature (T _N ) of 245 K. In the systematic study of strain effects, T _N changes significantly under strains from −4% to 4% when the antiferromagnetic ground state is not affected. And the compression strain can increase T _N to 469 K due to the enhancement of antiferromagnetic coupling of the nearest adjacent magnetic atoms. Moreover, the bandgap and T _N of monolayer Mn _2 Cl _8 can be tuned by hydrogenation. This work finds that elemental substitution, strains, and hydrogen passivation is efficient routes to tune the electronic properties of monolayer antiferromagnetic semiconductor Mn _2 Cl _8 .